Antiangiogenic AAV2 gene therapy with a truncated form of soluble VEGFR-2 reduces the growth of choroidal neovascularization in mice after intravitreal injection. (November 2022) - Puranen, Jooseppi; Koponen, Sanna; Nieminen, Tiina; Kanerva, Iiris; Kokki, Emmi; Toivanen, Pyry; Urtti, Arto; Ylä-Herttuala, Seppo; Ruponen, Marika
Abstract: Pathological angiogenesis related to neovascularization in the eye is mediated through vascular endothelial growth factors (VEGFs) and their receptors. Ocular neovascular-related diseases are mainly treated with anti-VEGF agents. In this study we evaluated the efficacy and safety of novel gene therapy using adeno associated virus 2 vector expressing a truncated form of soluble VEGF receptor-2 fused to the Fc-part of human IgG1 (AAV2-sVEGFR-2-Fc) to inhibit ocular neovascularization in laser induced choroidal neovascularization (CNV) in mice. The biological activity of sVEGFR-2-Fc was determined in vitro. It was shown that sVEGFR-2-Fc secreted from ARPE-19 cells was able to bind to VEGF-A165 and reduce VEGF-A165 induced cell growth and survival. A single intravitreal injection (IVT) of AAV2-sVEGFR-2-Fc (1 μl, 4.7 × 10 12 vg/ml) one-month prior laser photocoagulation did not cause any changes in the retinal morphology and significantly suppressed fluorescein leakage at 7, 14, 21 and 28 days post-lasering compared to controls. Macrophage infiltration was observed after the injection of both AAV2-sVEGFR-2-Fc and PBS. Our findings indicate that AAV2 mediated gene delivery of the sVEGFR-2-Fc efficiently reduces formation of CNV and could be developed to a therapeutic tool for the treatment of retinal diseases associated with neovascularization. Graphical abstract: Image 1 Highlights: Novel antiangiogenic gene therapy for the treatment of neovascular associated retinal diseases. AAV based fusion protein which combines the domains D1-D3 from human VEGFR-2. Long-term suppression of laser induced choroidal neovascularization in mice after intravitreal injection.